La balanza de pagos de Chile, Argentina Y Ecuador en los años 2019, 2020 Y 2021 - Morales Fassler, Eduardo Mateo (2022)
This research work analyzes the evolution of the Balance of Payments of Ecuador, Chile and Argentina in 2019, 2020 and 2021. For this purpose, quantitative research was proposed, with a descriptive approach, through the analysis of existing data from the Central Bank of Ecuador (BCE), Central Bank of Chile (BCCH) and Central Bank of Argentina (BCA) with a quarterly and annual periodicity. Through a horizontal financial analysis, the balance of payments accounts of each country was analyzed and then compared. Specifically, exports and imports of goods and services, current account, financial account, capital account, foreign direct investment account and income account were analyzed. The main results showed that Ecuador, compared to Chile and Argentina, is the only country with income from foreign direct investment in the years studied. Chile, in comparison with Ecuador and Argentina, is the country that exports and imports the most goods, maintaining. Chile seems to be ideal to establish an exporting company since the amount of money it handles and the positive evolution it presented in this account shows that they give priority to exports and this is combined with a competitive currency. While Ecuador is the most appropriate country to establish an importing company since it has advantages due to its strong currency and stability over time. Argentina is an appropriate destination for the rest of the world to sell services to as it was the account that showed the most activity.